Is Repeat PTA of a Failing Hemodialysis Fistula Durable? - Ioannis Bountouris; Thorarinn Kristmundsson; Nuno Dias; Zbigniew Zdanowski; Martin Malina (International Journal of Vascular Medicine)
Purpose. Our objective was to evaluate the outcome of percutaneous transluminal angioplasty (PTA) and particularly rePTA in a failing arteriovenous fistula (AV-fistula). Are multiple redilations worthwhile? Patients and Methods. All 159 stenoses of AV fistulas that were treated with PTA, with or without stenting, during 2008 and 2009, were included. Occluded fistulas that were dilated after successful thrombolysis were also included. Median age was 68 (interquartile range 61.5–78.5) years and 75% were male. Results. Seventy-nine (50%) of the primary PTAs required no further reintervention. The primary patency was 61% at 6 months and 42% at 12 months. Eighty (50%) of the stenoses needed at least one reintervention. Primary assisted patency (defined as patency after subsequent reinterventions) was 89% at 6 months and 85% at 12 months. The durability of repeated PTAs was similar to the durability of the primary PTA. However, an early primary PTA carried a higher risk for subsequent reinterventions. Successful dialysis was achieved after 98% of treatments. Nine percent of the stenoses eventually required surgical revision and 13% of the fistulas failed permanently. Conclusion. The present study suggests that most failing AV-fistulas can be salvaged endovascularly. Repeated PTA seems similarly durable as the primary PTA.